Special MVD-MGB Troops in Lithuania (1945–1959) - Pocius, Mindaugas (Genocidas ir rezistencija, 1997)
In 1950, V. Abakumov, Minister of State Security of the USSR, ordered the leadership of the LSSR MGB to: “use all means to solve the main task – to penetrate, through the agency, the centres, headquarters and other leadership units of bandits and nationalist formations, to find out their composition, hiding places and to detain all the participants or to physically destroy them”. The LSSR’s MGB carried out the order successfully in 1951–1953.
Keywords: repression structures; armed resistance; repressions